Sensibilidade insulínica e função da célula beta em indivíduos heterozigóticos para uma mutação no gene do receptor do GHRH - Rocha, Ívina Elaine dos Santos (2011)
GH and the insulin like growth factor type I (IGF-I) have synergistic functions on protein synthesis and muscle mass. In adipose tissue, GH stimulates lipolysis and lipid oxidation, while IGF-I stimulates the differentiation of pre adipocytes to adipocytes. In glucose metabolism , GH and IGF-I have antagonist opposite actions, been GH antagonist and IGF-I synergetic to insulin sensitivity (IS). Heterozygous adults individuals for the mutation c.104 = 1G> A in the GH releasing hormone receptor gene (MUT/N), present a mild reduction of GH and normal IGF-I levels accompanied by a significant reduction in lean body mass (Kg), with a tendancy of reduction in fat mass (kg), compared to homozygous normal adults individuals (N/N). IS and the beta cell function are unknown in individuals MUT/ N. To evaluate them, it was performed the oral glucose tolerance test with administration of 75g of glucose and serum glucose and insulin were measured at 0, 30, 60, 90, 120 and 180 minutes in 25 individual MUT/ N (12 M / 13 F, 40.08 ± 10.87 years) and 25 N/N (14 M / F 11; 39.96 ± 12.49 years). There was no difference in height, nevertheless weight, BMI, waist and hip circunferences were lower in individuals MUT/N. IS was assessed by HOMAir, where lower values indicate a greater IS and the QUICKI, OGIS 2 and OGIS 3, where higher values indicate higher SI. The beta cell function was assessed by HOMA-beta, insulinogenic index and area under the curve of insulin / glucose ratio (ASC I/G). ANOVA showed no difference between glucose and insulin responses between the groups. The areas under the curve of glucose and insulin were also similar between the number of patients with pre diabetes and diabetes. No changes were observed in the HOMAir, QUICKI, OGIS 2 and OGIS 3, HOMA beta, insulinogenic index and ASC I/G between the two groups. In conclusion, insulin sensitivity and beta cell function in MUT/N individuals are similar to MUT/N individuals.